THE DEVELOPMENT OF ARCHITECTURE AND FINE ARTS IN THE RENAISSANCE PERIOD IN EUROPE - Karimov Basriddin (Western European Studies, 2024)
The architecture of the Renaissance adopted ancient traditions, enriched it with new content, new architectural structures were created. High-rise buildings, magnificent mansions, public buildings of a new appearance rose. A new type of social-administrative center of the city appeared, related to the style and structure.
Keywords: Architecture; fine arts baroque; Leonardo da Vinci; Michelangelo